Impious Dogs, Haughty Foxes and Exquisite Fish - Pahlitzsch, Johannes,Schmidt, Tristan (De Gruyter, 2019)
This volume is dedicated to the topic of the human evaluation and interpretation of animals in ancient and medieval cultures. From a transcultural perspective contributions from Assyriology, Byzantine Studies, Classical Archaeology, Egyptology, German Medieval Studies and Jewish History look into the processes and mechanisms behind the transfer by people of certain values to animals, and the functions these animal-signs have within written, pictorial and performative forms of expression.
9783110576917
Keywords: Konferenzschrift; Tiere; Eigenschaft; Literatur